-2v-8=-3v

Simple and best practice solution for -2v-8=-3v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2v-8=-3v equation:


Simplifying
-2v + -8 = -3v

Reorder the terms:
-8 + -2v = -3v

Solving
-8 + -2v = -3v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '3v' to each side of the equation.
-8 + -2v + 3v = -3v + 3v

Combine like terms: -2v + 3v = 1v
-8 + 1v = -3v + 3v

Combine like terms: -3v + 3v = 0
-8 + 1v = 0

Add '8' to each side of the equation.
-8 + 8 + 1v = 0 + 8

Combine like terms: -8 + 8 = 0
0 + 1v = 0 + 8
1v = 0 + 8

Combine like terms: 0 + 8 = 8
1v = 8

Divide each side by '1'.
v = 8

Simplifying
v = 8

See similar equations:

| 18x=84-(7x+9) | | cot=-0.085 | | -19q+8(-4-7q)= | | x^2+kx+x+2k=0 | | x^3-9x=-6 | | 7-9j=4j-6 | | 7x=21-(49x-63) | | x^2-4x+y^2+z^2-6z-3=0 | | T^2+16t-36=0 | | 5-8u=-7u | | 8t-9=10t+9 | | 5x=31+2x+11 | | 6x+10-3x=8+2x-5 | | -r^2+8r=0 | | 2cosx-5=0 | | 3y+9=2y-4 | | 6+10-3x=8+2x-5 | | Y=5z-8 | | 15x+3(4x-6)=3x+9-9x | | (2x-4)+X=28 | | 7x=5+3x+19 | | 8h=10h+6 | | x^2-2x=19 | | 20+7n-6=7(2n+4) | | (x+14)(2x-7)=0 | | -5g=-10-3g | | x^2-2x=16 | | 5x+9=2x+48 | | 12=3(y-6)+3y | | -5q=-3q+10 | | 52x^2+13=0 | | 2x-4+x=28 |

Equations solver categories